2008
DOI: 10.1111/j.1742-7843.2008.00286.x
|View full text |Cite|
|
Sign up to set email alerts
|

Oestrogen Promotes Coronary Angiogenesis even under Normoxic Conditions

Abstract: Angiogenic therapy is one of the new treatments of ischaemic heart disease. Oestrogen has angiogenic properties under hypoxic condition, and if oestrogen also induces angiogenesis under normoxic condition, it could be used in combination with other angiogenic therapies in the treatment of ischaemic heart disease. In this study, we evaluated the angiogenic effect of high-dose oestrogen treatment in normoxic rat heart tissue. Fifty-two ovariectomized rats were randomized in oestrogen-treated and control groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…Estrogen has protective role on cardiovascular system,[21222324252627] however, its protective role in CP-induced nephrotoxicity is not well-established. The main objective of this study was to determine the role of estrogen in CP-induced nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen has protective role on cardiovascular system,[21222324252627] however, its protective role in CP-induced nephrotoxicity is not well-established. The main objective of this study was to determine the role of estrogen in CP-induced nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that EVs can prevent and reverse experimental pulmonary hypertension and that there is a miRNA signature of exosomes in human PAH that promotes vascular proliferation (12,13). E2 increases circulation of hematopoietic progenitors leading to microvessel growth in the heart and lungs (14)(15)(16)(17). The pro-inflammatory E2 metabolite 16-hydroxyestrone (16-OHE 1 ) as compared to the 2compounds (2-methoxyestrone [2-ME] and 2-methoxyestradiol) has been linked to cancer angioinvasion and PAH (18)(19)(20).…”
Section: Abstract Word Count: 250mentioning
confidence: 99%
“…The protective role of estrogen in cardiovascular system in women before menopause is well documented [42–47]. The incidence of chronic renal diseases is also gender related and is potentially higher in males [48, 49], which may relate to estrogen-mediated vascular endothelial growth factor [48].…”
Section: Introductionmentioning
confidence: 99%